On the resistance of steel ring-stiffened cylinders subjected to low-velocity mass impact. (October 2015) - Cerik, Burak Can; Shin, Hyun Kyoung; Cho, Sang-Rai
Abstract: This paper addresses the impact response of large-diameter thin-walled steel ring-stiffened cylinders subjected to low velocity mass impact and resulting local damage. Drop-weight impact tests with a striking mass, which had a knife-edge indenter, were conducted on two fabricated steel small-scale models. Details of the experiment setup, the procedure and the tests to obtain both quasi-static and dynamic material properties are described. With these observations, the experimental data, which include the final deformed shape, dynamic force-displacement curves and strain gauge measurements, are reported to be useful for future benchmark studies. The numerical prediction accuracy of the impact response of the test models were evaluated using the explicit solver of the finite element software package ABAQUS. The effect of the strain-rate hardening definition on the results is highlighted. Finally, the results that were obtained using a simplified analysis method based on smearing ring-stiffeners to obtain an equivalent circumferential bending strength were evaluated. The limitations of this simplified method were also discussed. Highlights: Drop-weight impact tests are conducted to investigate the response of ring-stiffened cylinders. Final deformed shape, dynamic force-displacement curves and strain gauge measurements are reported. Numerical simulations of the impact response of the test models are conducted. The influence of the strain-rate hardening definition on the numerical results is highlighted. A simplified analysis method is presented and validated with the test results.